MASKING USAGE OF PROCEDURAL GENERATION IN VIDEO GAMES - Tovstochub , Ihor; Zinchenko , Olha (Collection of scientific papers «ΛΌГOΣ», 2024)
In the video game development, procedural content generation (PCG) is a powerful technique for creating vast, dynamic game worlds. By using algorithms to generate game content on the fly, developers can create experiences that offer players a sense of discovery and novelty with each playthrough. Masking the usage of PCG is crucial for maintaining a cohesive and immersive gaming experience for players. If procedurally generated content is easily identifiable or stands out as distinct from handcrafted elements, it can disrupt the sense of immersion and suspension of disbelief that is essential for keeping gamers engaged. When PCG is effectively masked, players are unable to distinguish between procedurally generated and manually designed content, allowing them to remain fully immersed in the game world without breaking the illusion, at the same time allowing to decrease repetitive workload for the development team.